1996
DOI: 10.1063/1.362649
|View full text |Cite
|
Sign up to set email alerts
|

The application of the cathodic arc to plasma assisted chemical vapor deposition of carbon

Abstract: This article reports on the properties of hydrogenated carbon films deposited using a cathodic arc decomposition process with a graphite cathode used in a plasma assisted chemical vapor deposition mode. In this application of the cathodic arc, acetylene is broken down into radicals to form hydrogenated amorphous carbon films. Some results are also reported using hydrogen gas. The density in terms of plasmon energy or sp 3 fraction of the films has been found to decrease with increasing acetylene or hydrogen fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…9 There is much interest in all of these films due to their unique mechanical properties. 7,10 Recently, Yin et al 11 have found cauliflower-like growths ͑nanocrys-tals͒ which cannot be indexed to graphite in their FCVA deposited films, which are considered to be precursors for diamond growth. 12 However, there has been no published literature on the observation of diamond nanocrystallites in ta-C films deposited using the FCVA.…”
mentioning
confidence: 99%
“…9 There is much interest in all of these films due to their unique mechanical properties. 7,10 Recently, Yin et al 11 have found cauliflower-like growths ͑nanocrys-tals͒ which cannot be indexed to graphite in their FCVA deposited films, which are considered to be precursors for diamond growth. 12 However, there has been no published literature on the observation of diamond nanocrystallites in ta-C films deposited using the FCVA.…”
mentioning
confidence: 99%
“…Moreover, the ECR plasma remote from the substrate permits decoupled control of the energies of the ions striking the substrate by radio frequency ͑rf͒ biasing, which plays an important role in determining the film properties. [10][11][12] In this letter, vertically aligned multiwalled CNTs ͑MWNTs͒ are synthesized at temperatures as low as 400°C using ECR-CVD with rf biasing to the substrates. Our previous study 13 already showed that the morphologies of MWNTs varied with the negative self-bias voltages in rf biasing to the substrates, which resulted in the different degree of ordering of graphene layers in the CNT walls.…”
Section: Introductionmentioning
confidence: 99%